Stock Market Awareness of College Students in Pangasinan State University - Jameson N. Estrada; Dr. Erna M. Salazar; Dr. Randy Joy M. Ventayen (Southeast Asian Journal of Science and Technology, 2024)
The stock market has become a platform for investment and a significant aspect of the economy. In today's complex financial landscape, financial literacy is crucial for individuals especially young adults to make sound and wise decisions. College students are the future members of the labor force who will be responsible for managing their finances and investments. Hence, it is pivotal to assess their understanding of the stock market to identify the areas where they need further education and support. As such, this research sought to examine the stock market and investment awareness among college students in Pangasinan State University. The study utilized descriptive research and cluster sampling with a sample size of 221 students and administered a validated online survey questionnaire using Google Forms. The collected data were analyzed using statistical tools such as frequency, percentage, average weighted mean, Likert-scale, and Analysis of Variance. The results disclosed that most college students surveyed were female, fourth-year students aged 21 or older, with an average monthly family income of Php10,000 or less. Most respondents had no experience with stock investment and a neutral perception of it, with some showing potential interest in investing in the future, indicating a varying degree of interest in learning about the stock market. In terms of stock market awareness, the findings showed that the students had an average understanding of stock market concepts. Similarly, the awareness of stock market investment of college students is generally average. The study recommends that academic institutions should incorporate financial literacy courses in their curriculum and students must be encouraged to participate in stock-related activities to increase their knowledge and enhance their understanding of stock market investment.